KARAKTERISTIK PENDERITA MENINGITIS PADA ANAK DI RUANG RAWAT INAP DI RSUP H. ADAM MALIK MEDAN TAHUN 2014-2016 - Fitrah Fauziah; Sori Muda Sarumpaet; Fazidah A Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Meningitis is a health problem in the worldwide. Data World Health Organization (WHO) 2015 showed, more than 400 million people live in 26 countries infected meningitis annually. It causes 10% resulted in death, with 10-20% with neurological sequelae. The purpose of this study is to describe the characteristics of meningitis in children hospitalized in H. Adam Malik Medan Hospital 2014-2016. This is descriptive study with case series design. Population are children who suffer from meningitis on 2014-2016 with the amount of 110 children as a sample (total sampling). Data was analyzed by Chi square, Exact Fisher’s and T-test. The result of this study showed that highest number of meningitis in children found: 0-5 years old group (57.3%) with 1:1.5 ratio between male and female, Islam (60.9%), outside of Medan (83.6%), unconscious condition (52.7%), adequate nutritional status (60.0%), seizure disorder (53.6%), was a stiff neck (48.2%), type of purulenta meningitis (63.6%),length of stay 2 days (14.4%), death (47.3%). There was no significant difference sex and average of stay by classification, discharge condition by age, nutritional status by classification(p>0.05). There was significant difference age by classification, discharge condition by admittance condition and classification (p<0.05). It was recommended that parentsshould provide immunization Haemophilus influenzae (Hib) for infant and all children under five years old to prevent meningitis in children.